The Influence of Managerial Ability and Capital Structure on Firm Value: Cost of Equity as a Mediating Variable - Santoso, Clara Alverina; Ng, Suwandi (AJAR, 2026)
The purpose of this study was to investigate the effect of managerial ability and capital structure on cost of equity, the influence of managerial ability, capital structure and cost of equity on firm value and the mediating role of cost of equity on managerial ability and capital structure on firm value. The population used in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 2019 – 2021. The total sample was 178 companies for 3 years which were selected using a purposive sampling method. This study uses secondary data in the form of annual reports and financial reports obtained from the IDX database, yahoo finance, and the company's official website. The results of this study indicate that managerial ability and the capital structure of financial statements can increase the cost of equity. The findings also indicate that managerial ability and cost of equity can increase firm value, while capital structure can reduce firm value. These findings imply that companies must pay attention to debt management issues and managerial capabilities in increasing firm value because the company is always paid attention to by all stakeholders.